A systematic review of the literature and bibliometric analysis of governance of family firms - Pu, Zhongmin; Xu, Zeshui; Wang, Xinxin; Skare, Marinko (Journal of Business Economics and Management, 2022)
Governance in family firms can profoundly influence corporate behavior and performance. Recently, family firm governance (FFG) has attracted extensive attention as increasing empirical research has been published. However, few studies have attempted to map the global research on this growing field. In this paper, a comprehensive literature review and bibliometric analysis are conducted to provide an overview of the FFG. A total of 626 relevant studies from the Web of Sciences Core Collection database between 1998 and 2020 are analyzed. First, based on a literature review by identifying the classification of FFG and topics related to family governance, an overall conceptual structure is proposed. Second, the performance and influence of journals, authors and papers are analyzed by descriptive bibliometric analysis. Finally, with assistance from the CiteSpace and VoS viewer tools, the co-authorship, co-occurrence and co-citation network are presented to display the social and intellectual structure and find the hotspots. The findings of this study help to objectively understand the evolution of FFG and to capture potential research directions.